Unlocking the Willingness: Investigating the Factors Affecting Young Adults’ Intention to Donate Blood Stem Cells - Nombulelo Dilotsotlhe (Public Health Perspective Journal, 2026)
This study was conducted in South Africa to identify and understand the perceptions and attitudes of young adults towards blood stem cell donation. Despite a global rise in demand for blood stem cells, less than 1% of South Africans are registered donors, indicating a severe shortage. A cross-sectional quantitative survey was carried out among 276 young adults aged 18 to 35 years across various provinces. Data were collected on attitudes, subjective norms, perceived behavioural control, and intention towards blood stem cell donation. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with bootstrapping (5000 resamples). The results show that all three antecedents of the Theory of Planned Behaviour significantly influenced intention: attitude (β = 0.196, p < .001), subjective norm (β = 0.476, p < .001), and perceived behavioural control (β = 0.325, p < .001), explaining 41.2% of the variance in intention (R² = 0.412). These findings highlight that young adults who hold positive attitudes, feel social encouragement, and perceive control over the donation process are more likely to express willingness to donate. The study underscores the critical role of social marketing and awareness campaigns in enhancing donor participation and mitigating the blood stem cell shortage in South Africa.